2014
DOI: 10.1039/c4cp02276a
|View full text |Cite
|
Sign up to set email alerts
|

Morphological effects of the nanostructured ceria support on the activity and stability of CuO/CeO2 catalysts for the water-gas shift reaction

Abstract: Three CuO/CeO2 catalyst with different morphologies of ceria, namely nanospheres, nanorods and nanocubes, were synthesized and used to catalyze the water-gas shift (WGS) reaction. The reactivity tests showed that the Cu supported on the ceria nanospheres exhibited both the highest activity and superior stability when compared with the nanocube and nanorod ceria catalysts. Operando X-ray diffraction (XRD), X-ray absorption fine structure (XAFS) and diffuse reflectance Fourier transform infrared spectroscopy (DR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
135
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(144 citation statements)
references
References 58 publications
8
135
1
Order By: Relevance
“…Therefore, the obtained CeO 2 samples are ideal supports to investigate the crystal-plane effect on catalytic performance. Similar to the literature [21], the nanoshaped CeO 2 supports inherit their authentic morphologies after the loading of Cu. CuO particles were not resolvable from the TEM images because of the high dispersion of minute particles as well as the low contrast between the CuO and CeO 2 supports.…”
Section: Structural Characterization Of the Catalystssupporting
confidence: 60%
See 2 more Smart Citations
“…Therefore, the obtained CeO 2 samples are ideal supports to investigate the crystal-plane effect on catalytic performance. Similar to the literature [21], the nanoshaped CeO 2 supports inherit their authentic morphologies after the loading of Cu. CuO particles were not resolvable from the TEM images because of the high dispersion of minute particles as well as the low contrast between the CuO and CeO 2 supports.…”
Section: Structural Characterization Of the Catalystssupporting
confidence: 60%
“…The bands at 3729, 3686, and 3635 cm −1 can be assigned to mono, double, and triple coordinated hydroxyl [21]. At 250 °C, a strong broad band of hydroxyl centered at 3700 cm −1 was observed due to the strong interaction between hydroxyls through hydrogen bonding.…”
Section: The Catalytic Activities Of the Catalystsmentioning
confidence: 95%
See 1 more Smart Citation
“…Theoretical simulations predicted increasing catalytic activity of ceria nanorods in CO oxidation with increasing lattice microstrain [60]. It has been suggested that increasing microstrain enhances active metal-ceria support interaction, resulting in improved dispersion of the active phase, stabilization of the active metal species in a lower valence state and enhanced overall reducibility [27,61]. Supported ceria cubes were moreover reported to possess lower lattice microstrain and corresponding lower catalytic activity in WGS compared to rods [27].…”
Section: Discussionmentioning
confidence: 99%
“…Ceria is typically used for active support, as numerous research findings have indicated that such a characteristic is due to strong metal-ceria surface defects bonding, which stabilises the metal catalyst [18][19][20][21][22]. In this situation, ceria-metal interface will exist through oxygen migration from the support to the metal and vice versa, resulting in an enhanced surface reaction (e.g.…”
Section: +mentioning
confidence: 99%